Pharmacokinetic and Genomic Effects of Arsenite in Drinking Water on Mouse Lung in a 30-Day Exposure - Jaya Chilakapati; Kathleen Wallace; Araceli Hernandez-Zavala; Tanya Moore; Hongzu Ren; Kirk T. Kitchin (SAGE Publishing, 2015)
The 2 objectives of this subchronic study were to determine the arsenite drinking water exposure dependent increases in female C3H mouse liver and lung tissue arsenicals and to characterize the dose response (to 0, 0.05, 0.25, 1, 10, and 85 ppm arsenite in drinking water for 30 days and a purified AIN-93M diet) for genomic mouse lung expression patterns. Mouse lungs were analyzed for inorganic arsenic, monomethylated, and dimethylated arsenicals by hydride generation atomic absorption spectroscopy. The total lung mean arsenical levels were 1.4, 22.5, 30.1, 50.9, 105.3, and 316.4 ng/g lung tissue after 0, 0.05, 0.25, 1, 10, and 85 ppm, respectively. At 85 ppm, the total mean lung arsenical levels increased 14-fold and 131-fold when compared to either the lowest noncontrol dose (0.05 ppm) or the control dose, respectively. We found that arsenic exposure elicited minimal numbers of differentially expressed genes (DEGs; 77, 38, 90, 87, and 87 DEGs ) after 0.05, 0.25, 1, 10, and 85 ppm, respectively, which were associated with cardiovascular disease, development, differentiation, apoptosis, proliferation, and stress response. After 30 days of arsenite exposure, this study showed monotonic increases in mouse lung arsenical ( total arsenic and dimethylarsinic acid) concentrations but no clear dose-related increases in DEG numbers.